Systemic Exposure to Irradiated Apoptotic Cells Induces Autoantibody Production - Mevorach, Dror (The Rockefeller University Press, 1998)
During apoptotic cell death, cell surface ligands initiate phagocytosis of the dying cell. Clearance of these apoptotic cells is thought to occur without an immune response. Since a number of autoantigens are located at the cell surface or within apoptotic blebs, we examined whether exposure of mice to syngeneic apoptotic cells by the intravenous route could induce autoantibody production. Normal mice injected with syngeneic apoptotic thymocytes developed antinuclear autoantibodies and anticardiolipin and anti-ssDNA antibodies. The autoantibody levels were generally lower than those observed in MRL/Fas(lpr) mice and were transient. Surprisingly, six out of six immunized mice demonstrated immunoglobulin G deposition in the glomeruli several months after immunization. These findings indicate that systemic exposure to apoptotic cells can induce an immune response in normal mice, and may help to explain antigen selection and initiation of the immune response in diseases characterized by increased rates of apoptosis such as AIDS and, possibly, systemic lupus erythematosus.